THE DISTRIBUTION AND BIODIVERSITY OF FISHES IN LEBAK PAMPANGAN SWAMP SOUTH SUMATRA PROVINCE - Dina Muthmainah; Zulkifli Dahlan; Robiyanto H. Susanto; Abdul Karim Gaffar; Dwi P. Priadi (Research Center for Fisheries, 2013)
This research was conducted to evaluate the fish distribution and biodiversity within three types of swamp ecosystem with different water sources in Pampangan Sub-district during July to December 2011. The field observation were conducted in three different types of swamp. Ecological data and samples were collected from three sampling points in each swamp type. Parameters including local distribution, diversity index, similarity index, evenness and species richness, were analyzed. The results show a number of 9,723 fishes corresponding to 46 species were collected, the fish categorized into 16 families belonging to five orders. Eight species were found in all type of swamps i.e. Mystus nemurus, Channa striata, Cyclocheilchthys apogon, Cyclocheilichthys armatus, Pristolepis fasciata, Puntius lineatus, Osteochillus hasselti, and Trichogaster pectoralis. A diversity index of fishes in Pampangan Swamp ranged from 2.31 to 2.85, indicating moderate values. The evenness index was high more than 50%. The highest similarity was found between type 1 and type 3 of (0.43). The highest diversity index (2.85) found in type 2 of swamp indicates the swamp in more stable condition.